ENHANCING MATHEMATICS LITERACY IN VOCATIONAL SCHOOLS: THE KEY ROLE OF PEDAGOGICAL CONTENT KNOWLEDGE (PCK) AMONG TEACHERS: MENINGKATKAN LITERASI MATEMATIKA DI SMK: PERAN KUNCI PENGETAHUAN KONTEN PEDAGOGIS (PCK) DI KALANGAN GURU - Patimbangi, Andi; Kasmah; Hidayati, Rahma (MaPan : Jurnal Matematika dan Pembelajaran, 2023)
Pedagogical Content Knowledge (PCK) is an ability that is very necessary to improve students' mathematical literacy skills. For this reason, this research describes in depth the ability of Pedagogical Content Knowledge (PCK) teachers and the relationship between these abilities in building mathematical literacy. This type of research used a mixed method through data collection techniques using triangulation, namely interviews, observation, and questionnaires. The research results show that Pedagogical Content Knowledge (PCK) is still at level 1 in terms of the teaching knowledge component, student knowledge component, and content knowledge component. Besides that, the research results also found that Pedagogical Content Knowledge (PCK) teachers have a relationship with students' mathematical literacy skills. The better the ability of the Pedagogical Content Knowledge (PCK) teacher the greater the potential for students to have good mathematical literacy skills. One of the learning models needed to improve students' literacy skills is a learning model that can accommodate differences in student characteristics including differences in intelligence.